Isolation and sensitivity of cervical ganglion bacteria in guinea pigs (Cavia porcellus) with lymphadenitis in commercial family farms in Cajamarca, Peru - Vargas-Rocha, Luis (2023)
The aim of this study was to identify the etiological agent of lymphadenitis in guinea pigs from five commercial family breeding farms in Cajamarca, Peru, as well as to determine the sensitivity of the agents found against antibacterial frequently used in the area (amoxicillin, ciprofloxacin, nitrofurantoin, cephalexin, tetracycline, trimethoprim/sulfamethoxazole, and penicillin). Five guinea pigs with clinical signs of lymphadenitis were obtained and samples were taken from the affected cervical lymph nodes. Bacterial isolation was carried out on blood agar and MacConkey agar and the antibiogram was carried out according to the Kirby-Bauer method. The etiological agent was Trueperella pyogenes, highly sensitive to nitrofurantoin and resistant to penicillin.